The Integration of Children with Special Needs in the Regular Education - João Josué Silva Filho (Universidade Federal de Santa Catarina, 1999)
Although the constitution guarantees the right of citizens to education, a considerable portion of the Brazilian population to it, does not have access, particularly those with disabilities especiais.Como insert them into mainstream education?